Verbal Encoding Strategies in Visuo-Spatial Working Memory - Joana Pereira Seabra; Vivien Chopurian; Alessandra S. Souza; Thomas B. Christophel (Journal of Cognition)
Visual working memory and verbal storage are often investigated independently of one another. However, a growing body of evidence suggests that naming visual stimuli can provide an advantage in performance during visual working memory tasks. On the other hand, there is also evidence that labeling could lead to biases in recall. Here, we present an exploratory investigation of verbal labels associated with the memorization of simple visuo-spatial stimuli, and how the use of these labels informs recall behavior of the same stimuli in a separate working memory task. English-speaking participants performed a working memory task with orientation and location stimuli, followed by a separate naming task featuring the same stimuli. We found a diverse set of labels employed frequently and with a consistent distribution across stimulus types, the stimulus space, and among participants. The use of individual spatial words, predicted class 1 cardinal biases in memory (i.e. the observation that cardinal stimuli are more accurately recalled than non-cardinal ones). Conversely, words expressing uncertainty (e.g. ‘slightly’, ‘near’) predicted class 2 cardinal bias (i.e. recall biases away from the cardinal planes). This relationship between word use and recall biases is consistent with shared representational resources that are used for both visuo-spatial and verbal working memory.